Deprotonation of p-hydroxybenzoic acid: does electrospray ionization sample solution or gas-phase structures? - Schröder, Detlef; Buděšínský, Miloš; Roithová, Jana (Journal of the American Chemical Society, 2012)
Despite the simplicity of the molecule, the site of single deprotonation of p-hydroxybenzoic acid upon electrospray ionization (ESI) has recently formed a subject of debate in this journal. By means of NMR experiments in solution and gas-phase studies employing ion-mobility mass spectrometry (IM-MS), the apparent controversy is resolved. It is shown that irrespective of the solvent the carboxylate tautomer is preferred in solution, while the opposite holds true for isolated ions in the gas phase. The tautomer distribution sampled in the gas phase very much depends on the actual solvent used in ESI, the pH value, as well as the total concentration. Moreover, the occurrence of gas-phase reactions in the course of the ESI process influences the tautomer ratio. Implications for correlations between ESI mass spectra and solution-phase chemistry are discussed.